Respuesta :
The expansion would be 16x^4+32x^3+24x^2+8x+1
The coefficient would be 16
Hope I didn't mess up for your sake
The coefficient would be 16
Hope I didn't mess up for your sake
Consider the typical binomial expansion: (1 + x)ⁿ
[tex](1 + x)^{n} = \sum_{r=0}^{n} \left(\begin{array}{ccc}n\\r\end{array}\right)(1)^{n - r}(x)^{r}[/tex]
[tex]\therefore (1 + 2x)^{4} = \sum_{r=0}^{4} \left(\begin{array}{ccc}4\\r\end{array}\right)(1)^{4 - r}(2x)^{r}[/tex]
Since we need to find the coefficient of x⁴, then we need to let r = 4 in order to find the coefficient.
Thus, the coefficient is:
[tex]\left(\begin{array}{ccc}4\\4\end{array}\right)(1)^{4 - 4}(2x)^{4}[/tex]
[tex]= 16x^{4}[/tex]
Thus, the coefficient of x⁴ is 16.
[tex](1 + x)^{n} = \sum_{r=0}^{n} \left(\begin{array}{ccc}n\\r\end{array}\right)(1)^{n - r}(x)^{r}[/tex]
[tex]\therefore (1 + 2x)^{4} = \sum_{r=0}^{4} \left(\begin{array}{ccc}4\\r\end{array}\right)(1)^{4 - r}(2x)^{r}[/tex]
Since we need to find the coefficient of x⁴, then we need to let r = 4 in order to find the coefficient.
Thus, the coefficient is:
[tex]\left(\begin{array}{ccc}4\\4\end{array}\right)(1)^{4 - 4}(2x)^{4}[/tex]
[tex]= 16x^{4}[/tex]
Thus, the coefficient of x⁴ is 16.